Peran Penggunaan Second Account Instagram dalam Mengurangi Tekanan untuk Mengikuti Standar di Media Sosial pada Gen Z - Faaizah Syafara Zuhrah; Amiruddin Saleh; Harvia Atika Zahira (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Instagram has become a widely used social media platform for Gen Z to cultivate a self-image and gain social recognition. However, the pressure to portray an ideal life often leads to digital social pressure. This has prompted the use of